ANALISIS PENERAPAN PERLAKUAN DAN PENGUKURAN AKUNTANSI ASET TETAP MENURUT PSAK NO. 16 PADA RUMAH SAKIT ISLAM AMINAH DI KOTA BLITAR - Mega Dwi Lestari; Ahmad Fahrudin Alamsyah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to explain the application of accounting treatment and measurement of fixed assets according to PSAK NO. 16 at the Aminah Blitar Islamic Hospital. This research uses a qualitative descriptive type of research, describing the overall facts regarding the fixed asset accounting policy applied at the Aminah Blitar Islamic Hospital. The data sources used were interviews, direct observation and documentation. Based on the research results, it shows that the accounting treatment and measurement of fixed assets carried out by the Aminah Blitar Islamic Hospital, some of its practices are in accordance with the rules contained in PSAK NO. 16 however there are several improvements that need to be made.